2014
DOI: 10.1038/ncomms4519
|View full text |Cite
|
Sign up to set email alerts
|

A mechanical-force-driven physical vapour deposition approach to fabricating complex hydride nanostructures

Abstract: Nanoscale hydrides desorb and absorb hydrogen at faster rates and lower temperatures than bulk hydrides because of their high surface areas, abundant grain boundaries and short diffusion distances. No current methods exist for the direct fabrication of nanoscale complex hydrides (for example, alanates, borohydrides) with unique morphologies because of their extremely high reducibility, relatively low thermodynamic stability and complicated elemental composition. Here, we demonstrate a mechanical-force-driven p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 140 publications
(42 citation statements)
references
References 40 publications
1
40
0
1
Order By: Relevance
“…Therefore, good kinetics is essential for hydrogen storage. It is reported that reducing the size of hydrogen storage materials could lead to a remarkable change in hydrogen absorption/desorption kinetics [12,[38][39][40][41]. It is well proven that small particles of hydrides have an influence on hydrogen absorption/desorption kinetic properties, mainly due to shortened hydrogen diffusion and dissociation pathways, and enlarged surface free energy when the size decreases to below a few nanometers [42,43].…”
Section: Effect Of Downsizing On Kineticsmentioning
confidence: 99%
“…Therefore, good kinetics is essential for hydrogen storage. It is reported that reducing the size of hydrogen storage materials could lead to a remarkable change in hydrogen absorption/desorption kinetics [12,[38][39][40][41]. It is well proven that small particles of hydrides have an influence on hydrogen absorption/desorption kinetic properties, mainly due to shortened hydrogen diffusion and dissociation pathways, and enlarged surface free energy when the size decreases to below a few nanometers [42,43].…”
Section: Effect Of Downsizing On Kineticsmentioning
confidence: 99%
“…[1][2][3][4] However, both hydrogen production and storage are great challenges for realizing the so-called "hydrogen economy." [12][13][14][15][16][17][18] Unfortunately, no methods have been able to achieve the United States Department of Energy (DOE) standards for hydrogen storage so far. Furthermore, hydrogen storage is considered as a bottleneck for the dawn of hydrogen economy and it also attracts an extraordinary amount of research interest.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for the obtained destabilizations above can be understood from two aspects: (i) the NaBH 4 at a nanoscale level reduce the interdiffusion length of the constituents. This may accelerate mass transfer of the solid phases that is the common ratelimiting step for the dehydrogenation [32]; (ii) the nanosized NaBH 4 is thermodynamically less stable because of higher specific surface areas, abundant grain boundaries than the bulk one [26,33].…”
Section: Resultsmentioning
confidence: 99%